Divertimentos e tempo livre: experiências dos trabalhadores em Juiz de Fora (1900 – 1924) - Marina Fernandes Braga Nakayama (2016)
The current paper will shed light on the entertainment and free time of Juiz de Fora city workers in the beginning of the Twentieth Century as its main aim. Juiz de Fora had been characterized by progress and modernity, and amongst it, its contemporary entertainment. There were some sort of leisure which were sometimes allowed, sometimes rebuffed or even regulated by the city`s institutions. Thus, by analyzing a complex gathering of documents such as municipal administration, legislation requirements, newspapers, personal memory records and crime processes this search attempts to comprise the relation between entertainment and Juiz de Fora`s workers. This paper task, therefore, is to rebuild the scenary of leisure practices developed by the city’s workers, remembering that in such city the free market and free job were being structured along this time. By studying the described researched documental sources, it is possible to realize how there were so many social practices related to the city’s workers, which used to engender sociabilities networks, bonds and conflicts through urban and rural spaces where they dwelled.